Final-Year Students in Terms of Career Maturity and Employability - Pratiwi, Endah Andriani; Fatwa, Melynda (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
After completing their education at university, students will face a world that is much different from campus world. How mature these students are to start their career and their readiness to face the world of work are important things to research. This research was carried out with a quantitative approach to see the connection between these two variables. This research was conducted on 184 final-year students at the UNJANI Faculty of Psychology using Sample Random Sampling techniques. The measurements used are the Career Maturity Inventory-Form C questionnaire proposed by Crites & Savickas (2011) and the Employability questionnaire, which is an adaptation of the measuring tool created by Pool & Sewell (2007). Data processing is JASP 0.14.1.0 for Windows which uses Cronbach's Alpha coefficient, so the reliability test results of the measuring instrument are 0.924 and employability 0.975. The research results show that there is a low positive connection between Career Maturity and Employability (r = 0.147*, p < 0.05), meaning that there is a positive connection between Career Maturity and Employability. However, if the subject has high Career Maturity, it does not necessarily mean that his Employability is high as well. Currently, students with high Career Maturity are at 27.17%, medium ones are at 61.41% and low ones are at 11.41%. As for Employability, 16.4% of students are found to have high Employability, 69% are medium and 14.6% are low.